Syngas Production from Methane Dry Reforming over SmCoO3 Perovskite Catalyst: Kinetics and Mechanistic Studies - Osazuwa, Osarieme U.; Setiabudi, H. D.; Sureena, Abdullah; Cheng, C. K.
The kinetics of the methane dry (CO2) reforming over the SmCoO3was investigated in the temperature ranged 973e1073 K by varying the CH4and CO2partial pressures. Based on detailed study of the reaction mechanism, a mechanistic model is proposed from which a kinetic model is derived. The mechanistic pattern assumes adsorption of CH4on reduced Co, followed by methane cracking and carbon deposition. CO2 reacts with Sm2O3 to form Sm2O2CO3 and the oxycarbonates react with carbon to produce CO. The power law and LangmuireHinshelwood kinetic model which is established on this mechanism were able to forecast the kinetic results.